Plastic surgery : - Stone, Christopher (Cambridge University Press, 2001)
The FRCS(Plast) is the final examination taken by plastic surgery trainees towards the end of their training in the UK. This book has been written to address the needs of the candidate for this examination and non-UK equivalents. It provides comprehensive coverage of plastic surgery in a format that is easy for the trainee to assimilate rapidly and as such, will not only be indispensable as a revision guide but also as a valuable quick reference for the busy practising surgeon on the wards or in the consulting room. One key feature of the book which will enhance its use as a self-learning tool, is that it contains many sample examination questions with suggested answers